2019
DOI: 10.1111/grow.12355
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal pattern evolution and spatial spillover effect of green development efficiency: Evidence from Shandong Province, China

Abstract: Improving green development efficiency is urgently required, yet challenging, since it comprehensively reflects the bidirectional evolutionary relationship between regional development and resource and environmental consumption. The issue of regional green development efficiency has become a key topic; however, where the increase in efficiency originates and its spatial spillover effect remains unclear to date. Therefore, the spatial spillover effect of the green development efficiency of Shandong Province was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Green development efficiency integrally reflects the coordinated development among the three systems of economy, society, and ecological environment, which not only considers the allocation efficiency of input and output factors in the process of economic and social development but also considers the pollution of the ecological environment. Based on the above green development system theory, input-output model, and the established research [ 4 , 7 , 44 , 45 ]; the index system of labor, fixed assets, energy consumption, water supply, and land use as input indicators; economic output, ecological environment, and social output as desired outputs; and wastewater emission, smoke and dust emission, exhaust gas emission, and air pollution as nonconsensual outputs are used to measure green development efficiency. Table 2 presents the evaluation index system for green development efficiency.…”
Section: Evaluation Index System For Green Development Performancementioning
confidence: 99%
“…Green development efficiency integrally reflects the coordinated development among the three systems of economy, society, and ecological environment, which not only considers the allocation efficiency of input and output factors in the process of economic and social development but also considers the pollution of the ecological environment. Based on the above green development system theory, input-output model, and the established research [ 4 , 7 , 44 , 45 ]; the index system of labor, fixed assets, energy consumption, water supply, and land use as input indicators; economic output, ecological environment, and social output as desired outputs; and wastewater emission, smoke and dust emission, exhaust gas emission, and air pollution as nonconsensual outputs are used to measure green development efficiency. Table 2 presents the evaluation index system for green development efficiency.…”
Section: Evaluation Index System For Green Development Performancementioning
confidence: 99%
“…The second research direction investigates spatial heterogeneity and the mechanisms influencing green development. The study of the spatial heterogeneity of green development has a diversified range, covering countries [29][30][31][32], typical regions and provinces [33,34], and typical cities [35,36]. Research on the influencing factors and driving factors of green development involves economic development, industrial structure, urbanization, financial tools, financial support, environmental regulation, public behavior, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the influencing factors and driving factors of green development involves economic development, industrial structure, urbanization, financial tools, financial support, environmental regulation, public behavior, etc. The main research methods are spatial autocorrelation analysis [36], IV_2SLS mode [37], LMDI model [38], spatial autoregressive model [39], Geodetector [40], GWR model [41], factor analysis model [17], spatial Durbin model [20], panel threshold regression [21] and Tobit model [22]. In the aspect of rural green development, Yu et al (2018) indicated that GDP per capita, urbanization, agricultural science and technology level and farmers' investment capacity are important influencing factors of rural green development [42].…”
Section: Introductionmentioning
confidence: 99%
“…The key to a regional green development lies in the improvement of green development efficiency, which can promote the transformation of a regional green development in the direction of sustainable development [6][7][8]. The green development efficiency is based on the essential principle of maximizing economic and social benefits or minimizing ecological damage, taking the coordinated development of economy, society and ecology as the fundamental requirement of resource input-output structural results, it improves the defects of traditional efficiency evaluation, which only considers the increase of material input, while ignoring the pursuit of scale expansion and total growth under the case of environment and energy constraints [9][10][11]. At present, the relevant green development efficiency measurement methods mainly include the comprehensive index method and the model evaluation method.…”
Section: Introductionmentioning
confidence: 99%